Risk factors for parasitosis in children under five years of age in a human settlement-Peru, 2020 (Revista Venezolana de Salud Pública, 2021)
To determine the risk factors for parasitosis in children under 5 years of age in a Human Settlement - Peru, 2020. An analytical, observational, prospective study was carried out; with a cross-sectional, relational design with a quantitative approach in 90 children and mothers applying a questionnaire of risk factors and to determine parasitosis. It was carried out through the analysis of small stool samples. Likewise, for the data analysis the descriptive statistics of the SPSS version 25 program was used and for the inferential analysis the bivariate analysis of the chi-square test was used with a significance of p
Keywords: Perú; Risk factors; intestinal parasites